2021
DOI: 10.3390/machines9110292
|View full text |Cite
|
Sign up to set email alerts
|

New FMEA Risks Ranking Approach Utilizing Four Fuzzy Logic Systems

Abstract: Process equipment and plant maintenance problems are complex in the oil refinery business, since effective maintenance needs to ensure the reliability and availability of the plant. Failure Mode and Effects Analysis (FMEA) is a risk assessment tool that aims to determine possible failure modes, and to reduce the ratio of unknown failure modes, by identifying business-critical systems and the risks of their failures. For the identified failure modes, FMEA determines risk mitigation action(s). The goal is to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is due to the fact that the importance of the scores (S,O,D) are very similar, at least theoretically, when, in real life, this is not the case. For this reason, we have decided to combine the FMEA approach with the fuzzy logic technique, which should yield a single output based on various input data [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the fact that the importance of the scores (S,O,D) are very similar, at least theoretically, when, in real life, this is not the case. For this reason, we have decided to combine the FMEA approach with the fuzzy logic technique, which should yield a single output based on various input data [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, three different formulas are proposed for the PRISM number calculation, as shown by Equations ( 8)- (10). Note that, the PRISM method is for considering partial risks, no formula is previously given for any calculations.…”
Section: The Characteristics Have the Following Valuesmentioning
confidence: 99%
“…Typically, the aim is to combine the strength of the risk assessment methodologies in this case. Throughout the decades of development, the reliability, effectiveness, usefulness, applicability, etc., of the platform risk assessment methodologies were significantly increased by dominantly mathematic-based methodological developments [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Drawbacks of the conventional FMECA method are also addressed in Ref. [33] by examples in the oil refinery field, providing a new fuzzy risk quantification approach method, "four fuzzy logic system", that includes pre-assessment by sets of fuzzy logic systems.…”
Section: State Of the Artmentioning
confidence: 99%